Inward Foreign Direct Investment and Economic Development in Tanzania - Kabyemera, Dorina Josiah (2008)
This study examines the role of inward foreign direct investment (FDI) and economic development in Tanzania. The paper studies the determinant and effects of foreign direct investment in the country. Therefore, focus will be on the probable factors leading to economic growth in Tanzania, as well as the dynamic effects of FDI inflow and its contributions to economic development of the country. The prominence of the study, will locate the problem and factors that contribute to FDI inflow in Tanzania. Accordingly, empirical study was carried out in this work. Thus, help me to confer the analysis part of this research, which include data collected from 1970 – 2006 respectively to fulfil my study. Besides, to carry out the empirical tests, the Eviews 6.0 software was applied to run the Unit root Tests, the granger causality tests and Vector Error Correction model (VECM). Moreover, under the research method employed, the tests undertaken to examine variables of the growth trend and FDI inflow in Tanzania with other variables such as, Human Capital, Information and communication technology (ICT), Employment and Import to signify economic development in Tanzania. Consequently, data collected, and the empirical results presented, indicate that there is a positive long– run relationship between economic growth and other variables in my model. Similarly, the significant effects of inward FDI on economic development in Tanzania was imports, employment and information and communication technology. However, the short-run empirical result indicates that there is no significant effect between growth and the other variables examined.